PEMBERIAN HAK ASUH ANAK DALAM PERCERAIAN KARENA PERALIHAN AGAMA (MURTAD) - Muhammad Khoirur Rofiq (UIN Walisongo Semarang, 2021)
Divorce due to apostasy causes child custody issues, is religion or the welfare of the child a priority? This study is a qualitative normative legal research with a juridical approach and a case approach. Primary data in this study are seven decisions of the Religious Courts regarding divorce by apostate parents and the determination of child custody. This paper focuses on examining (1) judges' considerations in determining custody of children in divorce due to apostasy, (2) patterns of granting custody of children in divorce due to apostasy. This research results in (1) The judge considers the conditions of the parties with three priority conditions for determining child custody, namely Islam, morals, and the ability to care for children. (2) the pattern of granting custody of children in divorce due to apostasy is (a) Islam becomes a priority requirement in determining child custody (b) if Islamic requirements are not met, then the moral requirements and the ability to care for the benefit of the child will be prioritized. The panel of judges will analyze the conditions of both parents to determine what is best for the child, even though custody is given to the apostate parent.